Lateral heterogeneity of dipalmitoylphosphatidylethanolamine-cholesterol Langmuir-Blodgett films investigated with imaging time-of-flight secondary ion mass spectrometry and atomic force microscopy - McQuaw, Carolyn M (Langmuir : the ACS journal of surfaces and colloids, 2005)
To better understand the influence of cholesterol (CH) on dipalmitoylphosphatidylethanolamine (DPPE), Langmuir-Blodgett (LB) model membranes of DPPE with varying amounts of cholesterol were imaged by time-of-flight secondary ion mass spectrometry (ToF-SIMS) and atomic force microscopy (AFM). Cholesterol has a condensing effect on DPPE that at low cholesterol concentrations results in lateral heterogeneity of the LB monolayer. At 4:1 DPPE/CH, islands of DPPE/CH phase exist with a connected DPPE phase. As the concentration of cholesterol is increased, the percolation threshold is crossed and the DPPE/CH phase islands connect to separate the DPPE phase (2:1 DPPE/CH). Finally, at 50 mol % cholesterol a single homogeneous DPPE/CH phase LB monolayer exists. ToF-SIMS of the DPPE/CH phase provides a lower ion signal for the characteristic lipid fragments and substrate apparently owing to the higher molecular density induced by cholesterol. AFM data indicate that the DPPE/CH phase is lower in height than the DPPE phase. As phosphatidylethanolamine is predominant in the inner lipid leaflet of cellular membranes, this work has implications for the understanding of cholesterol domains in the inner leaflet of cells